Efektivitas E-Procurement dalam Pengadaan Barang dan Jasa di Kota Pematang Siantar - Arthur Jonathan Purba; Siti Hazzah Nur. R (Lembaga Pengembangan Kinerja Dosen, 2026)
Government procurement plays a strategic role in supporting effective, efficient, transparent, and accountable public administration. To promote procurement reform, the government has implemented an electronic procurement system through the Electronic Procurement Service (LPSE). The implementation of the Electronic Procurement System (SPSE) in Pematang Siantar City aims to improve procurement quality, reduce irregularities, and accelerate the delivery of goods and services. However, several challenges persist, including limited human resources capable of operating the system, technical disruptions, lack of outreach to local vendors, and weak coordination between the Procurement Unit (UKPBJ) and related agencies. This study aims to analyze the effectiveness of SPSE implementation in Pematang Siantar City. The research uses a descriptive qualitative approach. Data were collected through interviews with UKPBJ officials and procurement officers from several local government units, direct observation of procurement activities via SPSE, and documentation review. Data analysis employed Duncan’s effectiveness indicators: goal attainment, integration, and adaptation. The results show that SPSE implementation has not been fully effective. In terms of goal attainment, procurement processes follow established procedures, but delays still occur due to system disruptions and limited user competence. In terms of integration, coordination between UKPBJ and technical units remains suboptimal, affecting communication and oversight. Regarding adaptation, although the information technology infrastructure is adequate, human resource capacity is still limited. Therefore, improving human resources, strengthening coordination, and enhancing system reliability are necessary to achieve optimal effectiveness.